Endovascular Thrombectomy for Acute Ischemic Strokes: Current US Access Paradigms and Optimization Methodology. Issue 4 (April 2020) - Sarraj, Amrou; Savitz, Sean; Pujara, Deep; Kamal, Haris; Carroll, Kirsten; Shaker, Faris; Reddy, Sujan; Parsha, Kaushik; Fournier, Lauren E.; Jones, Erica M.; Sharrief, Anjail; Martin-Schild, Sheryl; et al.
Abstract : Background and Purpose—: Timely access to endovascular thrombectomy (EVT) centers is vital for best acute ischemic stroke outcomes. Methods—: US stroke-treating centers were mapped utilizing geo-mapping and stratified into non-EVT or EVT if they reported ≥1 acute ischemic stroke thrombectomy code in 2017 to Center for Medicare and Medicaid Services. Direct EVT-access, defined as the population with the closest facility being an EVT-center, was calculated from validated trauma-models adapted for stroke. Current 15- and 30-minute access were described nationwide and at state-level with emphasis on 4 states (TX, NY, CA, IL). Two optimization models were utilized. Model-A used a greedy algorithm to capture the largest population with direct access when flipping 10% and 20% non-EVT to EVT-centers to maximize access. Model-B used bypassing methodology to directly transport patients to the nearest EVT centers if the drive-time difference from the geo-centroid to hospital was within 15 minutes from the geo-centroid to the closest non-EVT center. Results—: Of 1941 stroke-centers, 713 (37%) were EVT. Approximately 61 million (19.8%) Americans have direct EVT access within 15 minutes while 95 million (30.9%) within 30 minutes. There were 65 (43%) EVT centers in TX with 22% of the population currently within 15-minute access. Flipping 10% hospitals with top population density improved access to 30.8%, while bypassing resulted in 45.5% having direct access to EVT centers. Similar results were found in NY (current, 20.9%; flipping, 34.7%; bypassing, 50.4%), CA (current, 25.5%; flipping, 37.3%; bypassing, 53.9%), and IL (current, 15.3%; flipping, 21.9%; bypassing, 34.6%). Nationwide, the current direct access within 15 minutes of 19.8% increased by 7.5% by flipping the top 10% non-EVT to EVT-capable in all states. Bypassing non-EVT centers by 15 minutes resulted in a 16.7% gain in coverage. Conclusions—: EVT-access within 15 minutes is limited to less than one-fifth of the US population. Optimization methodologies that increase EVT centers or bypass non-EVT to the closest EVT center both showed enhanced access. Results varied by states based on the population size and density. However, bypass showed more potential for maximizing direct EVT-access. National and state efforts should focus on identifying gaps and tailoring solutions to improve EVT-access. Abstract : Supplemental Digital Content is available in the text.